The Influence of Motivation, Leadership, and Competence on Teacher Performance - Amaliah Ma'ruf; Gatot Puspita Aji; Samtirta Praswara (Manunggal Halim Jaya, 2022)
The purpose of this study was to examine the influence of teacher motivation (X1), principal leadership (X2), and teacher competence (X3) on teacher performance (Y). The population taken was 79 people and because the population was less than 100 people, the sample taken was the entire population as a total sample, namely all teachers at SMPN 2 Sungguminasa, and a tool to test data analysis using linear regression. The results of this study stated that partially the motivation variable (XI) showed a value of p = 0.001 <0.05, this means that partially the work motivation variable has a significant influence on the performance of SMP Negeri 2 Sungguminasa employees. Partially the leadership variable (X2) shows a value of p = 0.000 < 0.05. This means that partially the variable of workability has a significant employee performance and function at SMP Negeri 2 Sungguminasa. Competence has a significant effect on teacher performance with P = 0.000 < 0.05 with a coefficient value of 0.186. The coefficient shows that the better the level of educators, the better the performance, so the third hypothesis can be concluded that if there is an increase in the level of education and training, it will affect the Performance of the teacher. The variable that has the most dominant influence on teachers at SMP Negeri 2 Sungguminasa is motivation. Motivation and appreciation can encourage teacher performance. Training education is held under their duties and responsibilities, so that it can run effectively as well as efficiently and will make the teacher's performance level higher.